Dialog Pemikiran Pendidikan John Calvin Dan Kurikulum Merdeka: Implikasinya Bagi Pendidikan Agama Kristen Di Indonesia - Febrianus Selvin Sudiman; Herman Pakiding (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2026)
This article examines the dialogue between John Calvin’s educational thought and the Merdeka Curriculum within the context of Christian Religious Education (PAK) in Indonesia. Employing a qualitative-comparative approach with descriptive analysis, this study traces the points of convergence and tension between Calvin’s educational principles particularly the concept of imago Dei, holistic education, and the God-centered purpose of education and the principles of the Merdeka Curriculum such as flexibility, differentiated learning, and the Profil Pelajar Pancasila (Pancasila Student Profile). The analysis reveals significant convergence in terms of respect for the potential and uniqueness of learners, holistic educational orientation, and the role of teachers as facilitators and character formers. However, fundamental tensions also exist regarding Calvin’s theocentric theological foundation vis-à-vis the secular Pancasila foundation, the concept of discipline and authority versus student freedom, and the ultimate goal of education glorifying God versus forming the Pancasila Student Profile. Based on these findings, this article offers practical recommendations for PAK curriculum design based on the Merdeka Curriculum, a Kingdom of God-nuanced project-based learning approach, holistic assessment, and Christian character formation within the Profil Pelajar Pancasila framework. This research contributes to filling the gap in studies that dialogue the Reformed theological tradition with contemporary Indonesian national education policy.